Rethinking development in post-colonial Zimbabwe: the case of the CAMPFIRE Programme in Kanyemba - Maheve, Neil Batsirai (Rhodes University, Faculty of Humanities, Department of Political and International Studies)
This study is concerned with people's attitudes towards the Communal Areas Management Programme for Indigenous Resources (CAMPFIRE). This study is situated in Kanyemba, a ward in Mbire District, Mashonaland Central, Zimbabwe. CAMPFIRE is a community-based natural resource management programme that aims at empowering local communities to sustainably manage and benefit from wildlife and other natural resources within their confines. This study explores people's attitudes towards development (and CAMPFIRE as a development programme) and how they perceive, engage with, and contest development. There are two subgroups living in Kanyemba: the Chikunda, which is the majority group, and the Tembo Mvura. Rooted in post-development thinking, this study highlights the nuances and ambiguities in people's attitudes towards development. The study relies on interviews, participant observation, and archival material. The study has three guiding objectives. Firstly, I set out to explore how the Tembo Mvura and Chikunda community members living in Kanyemba perceive and interact with the CAMPFIRE programme and how their views coincide with or diverge from mainstream development discourse. The study discusses the Tembo Mvura and Chikunda definitions and descriptions of development and the two groups' perspectives and experiences of the CAMPFIRE programme. While the Tembo Mvura have mostly negative attitudes towards CAMPFIRE, their Chikunda neighbours exude both positive and negative attitudes towards development, projecting a sense of joy and appreciation but also disillusionment with development. Secondly, I highlight how Tembo Mvura and Chikunda actively participate in and challenge the CAMPFIRE project and how these interactions can be interpreted within the framework of post-development theory. As I explore these attitudes, I portray the ambivalence evident in people's simultaneous desire for and dismissal of development. While the people dismiss some aspects of development, they still want some development, hence the ambivalence. Finally, I explore how the residents of Kanyemba have responded to the limitations of CAMPFIRE, what alternatives to development they propose, and what role cultural, historical, economic, and environmental factors play in shaping the communities' alternatives to development. The residents of Kanyemba have different historical and cultural backgrounds, and I highlight how these have influenced the different alternatives to development proposed by Tembo Mvura and Chikunda. In this regard, I explore the nuanced critiques of development held by residents of Kanyemba, examining how cultural and historical factors influence their selective engagement with different aspects of the CAMPFIRE initiative. This thesis contributes to post-development thinking by arguing that the ambivalence evident in people's attitudes towards development in Kanyemba makes dismissing development more complicated than some post-development theorists suggest. The findings of the study show that people's ambivalence towards development emanates from CAMPFIRE's approach that strips individuals of agency, stifles their voices, and curtails democratic participation in determining their preferences and how they desire to progress.
Keywords: CAMPFIRE (Program); Postdevelopment theory; Rethinking; Kanyemba/Chapoto Ward (Zimbabwe); Natural resources -- Management; Community development -- Zimbabwe -- Kanyemba/Chapoto Ward